Functional analysis of candidate effector proteins during Sporisorium scitamineum x sugarcane interaction - Silva, Natália de Sousa Teixeira e (2019)
Sugarcane smut is a worldwide distributed disease important to agribusiness, since it can affect sugarcane yield drastically. The disease is caused by the Basidiomycete Sporisorium scitamineum, a biotrophic fungus that colonizes mainly sugarcane. Sugarcane-smut interaction has been extensively studied by this research group for the past few years in their various aspects, considering both the pathogen attack and plant defenses. This work aimed to functionally address fungal candidate effector proteins associated with this pathosystem. Effectors are essential to modulate host metabolism to allow pathogen colonization. The identification of such proteins may assist in recognition of resistance genes relevant to genetic breeding programs. Based on the complete genome sequence of S. scitamineum and the dual transcriptomic data candidate genes were selected in silico. Selection strategies were based on the predicted secretome and differential expression levels of the genes in planta. Candidate effectors were analyzed regarding their expression pattern, subcellular location and influence over basal plant defenses and plant immunity. The results showed that the S. scitamineum candidate effector genes are expressed under the influence of the host genotype. It was observed various expression patterns in the set of selected genes and differential subcellular localization patterns. These results will enable future researches considering virulence level of different isolates and also help decision making in plant breeding programs.